2023
DOI: 10.1038/s41467-023-38173-6
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of an Ala-rich C-degron by the E3 ligase Pirh2

Abstract: The ribosome-associated quality-control (RQC) pathway degrades aberrant nascent polypeptides arising from ribosome stalling during translation. In mammals, the E3 ligase Pirh2 mediates the degradation of aberrant nascent polypeptides by targeting the C-terminal polyalanine degrons (polyAla/C-degrons). Here, we present the crystal structure of Pirh2 bound to the polyAla/C-degron, which shows that the N-terminal domain and the RING domain of Pirh2 form a narrow groove encapsulating the alanine residues of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The nuclease Vms1/ANKZF1 and peptidyl-tRNA hydrolases have been proposed to cleave the P-site tRNA and facilitate NC release [26][27][28][29] . Once off the ribosome, CAT tails act as C-terminal degrons that mark stalled NCs for proteasomal degradation, serving as a backup pathway in case Ltn1p does not successfully target the NC 22,[30][31][32] (Figure 1A). In bacteria, CAT tails function as degrons 13,18 and have been proposed to enhance NC release from the large ribosomal subunit 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The nuclease Vms1/ANKZF1 and peptidyl-tRNA hydrolases have been proposed to cleave the P-site tRNA and facilitate NC release [26][27][28][29] . Once off the ribosome, CAT tails act as C-terminal degrons that mark stalled NCs for proteasomal degradation, serving as a backup pathway in case Ltn1p does not successfully target the NC 22,[30][31][32] (Figure 1A). In bacteria, CAT tails function as degrons 13,18 and have been proposed to enhance NC release from the large ribosomal subunit 29 .…”
Section: Introductionmentioning
confidence: 99%
“…KLHDC2 binds to C-degrons ending with diglycine ( 17 , 18 ); FEM1B and FEM1A/1C recognize C-degrons ending with arginine (Arg/C-degrons), with upstream sequences playing a role in selectivity ( 19 21 ). Very recently, it was reported that Cereblon, the SR of CRL4, targets the C-terminal cyclic imide degron( 22 ), Gln/C-degron is recognized by TRIM7 ( 23 , 24 ), Ala tails function as C-degron to recruit CRL2 KLHDC10 or Pirh2 ( 25 , 26 ), and CRL4 DCAF12 targets di-Glu C-degron ( 27 ). In the above C-degron pathway branches, sequence-specific C-terminal residues are engaged by an SR of the multisubunit E3 ligase or a functional domain of a single E3 ligase.…”
mentioning
confidence: 99%